Burnout and quality of life in nursing staff during the COVID-19 pandemic - Meneguin, Silmara [UNESP]; Ignácio, Isabelle [UNESP]; Pollo, Camila Fernandes [UNESP]; Honório, Heitor Marques; Patini, Mayara Salles Gasparini [UNESP]; de Oliveira, Cesar (Springer Nature, 2023)
Objective: To investigate the association between burnout and quality of life among nursing staff at intensive care units during the new coronavirus pandemic and identify the influence of sociodemographic variables. Methods: A cross-sectional study was conducted with 109 nursing staff members at intensive care units of a public hospital in Brazil. Data collection involved the administration of a sociodemographic questionnaire as well as the WHOQOL-Bref and Oldenburg Burnout Inventory. Results: The participants presented a high state of burnout and a low score in the physical domain of the quality-of-life instrument. Men (p = 0.037), income (p = 0.011) and burnout (p < 0.001) independently influenced quality-of-life (p < 0.01). Age, being a nursing technician and working at two hospitals exerted an influence on burnout status (p < 0.05). A negative association was found between quality of life and burnout (p < 0.01). Conclusion: Our findings showed that burnout due to occupational circumstances affected negatively the quality of life perceptions of nursing staff working at intensive care units during the COVID-19 pandemic.
Keywords: Burnout; Coronavirus; COVID-19; Nursing; Quality of life